Analisis Peran Rusia sebagai Mediator dalam Penyelesaian Konflik Nagorno Karabakh Periode 2008-2016 - Andhika Dewantara; Muhammad Yamin (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2019)
The Nagorno Karabakh conflict is a conflict over territorial disputes that is synonymous with inter-Azerbaijan strife that adheres to the principle of integrating its territory in Nagorno Karabakh and Armenia which support the Nagorno Karabakh region and ethnic Armenians who are in it for independence from Azerbaijan. The dynamics of the Nagorno Karabakh conflict between Azerbaijan and Armenia continue to unfold, and there has never been a sustainable peace agreement between the two parties in dispute since the peace agreement Bishkek (Bishkek Protocol) 1994. Along with the dynamics of the battle, Russia has a very active role in the mediation and peace-building process between the two parties in conflict. Russia's position as mediator is carried out within the official framework of the OSCE Minsk Group and in the personal initiation of the state in the medium of the trilateral meeting. This research will describe the dynamics of the Nagorno Karabakh conflict in the period 2008-2016 along with efforts to resolve disputes under the Russian role. Keywords : Nagorno Karabakh Conflict, Russia, Mediation, and Contigency Model